2015
DOI: 10.1186/s12865-015-0087-y
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 autoantibodies increase vasogenic edema formation and infarct size in a rat stroke model

Abstract: BackgroundNeuromyelitis optica (NMO) is an autoimmune disorder of the central nervous system, which is characterized by autoantibodies directed against the water channel aquaporin-4 (AQP4). As one of the main water regulators in the central nervous system, APQ4 is supposed to be involved in the dynamics of brain edema. Cerebral edema seriously affects clinical outcome after ischemic stroke; we therefore aimed to investigate whether NMO-antibodies may exert the same functional effects as an AQP4-inhibitor in-vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
(54 reference statements)
0
8
0
1
Order By: Relevance
“… [6] In a rat model, AQP4 antibodies have been demonstrated to worsen edema in the event of an ischemic stroke. [7] Furthermore, AQP4 antibodies may also damage the structural integrity of astrocytes by way of some immunoregulatory pathway, such as the activation of the classical complement cascade, or granulocyte recruitment, which consequently increases blood brain barrier (BBB) permeability. [8] It should also be noted that AQP4-dependent water flow through the cell membrane is an important mechanism for angioedema alleviation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… [6] In a rat model, AQP4 antibodies have been demonstrated to worsen edema in the event of an ischemic stroke. [7] Furthermore, AQP4 antibodies may also damage the structural integrity of astrocytes by way of some immunoregulatory pathway, such as the activation of the classical complement cascade, or granulocyte recruitment, which consequently increases blood brain barrier (BBB) permeability. [8] It should also be noted that AQP4-dependent water flow through the cell membrane is an important mechanism for angioedema alleviation.…”
Section: Discussionmentioning
confidence: 99%
“… [9] Once a cerebral infarction occurs, AQP4 antibodies can also down-regulate the expression of the glutamate transporter EAAT2, which causes glutamate circulation disorders and results in a more severe infarction. [7] …”
Section: Discussionmentioning
confidence: 99%
“…Nishiyama et al suggested that certain immunologic events that increase in the Blood brain barrier (BBB) permeability are needed to allow entry and binding to AQP4 on astrocytes [11]. Recently, however, Jueneman et al reported that in a rat stroke model, the animal infused with AQP4 antibodies suffered more vasogenic edema formation as compared to the controls, and that the size of the infarct was larger in the AQP4 antibody infused animals [12].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were obtained at the level of the maximum lateral displacement of the ventricle. MLS was calculated using the following equation: MLS = (A − B)/2, as described previously [ 23 ].…”
Section: Methodsmentioning
confidence: 99%